Study about the abusive use of electronic cigarette by college students (Research, Society and Development, 2022)
The first commercialized e-cigarette was produced in 2003 by a Chinese pharmacist, Hon Lik, who had been a smoker since the age of 18, created with the aim of helping other people to quit smoking. Interestingly, Hon Lik never stopped smoking e-cigarettes or conventional tobacco. Nowadays the market is full of electronic cigarettes that work with a liquid, consisting of chemicals and nicotine, which is heated by a battery and then vaporized and inhaled by the user. It is noteworthy that electronic cigarettes are called by other names on a daily basis such as pod, vape and e-cigarette. In that regard, this research aims to explore the harmful effects of abusive use of electronic cigarettes, exploring the lack of state regulation, the false idea that the product helps to stop smoking and what motivated students to start smoking. Therefore, to know the reality of university students, a questionnaire was applied to students of Medicine, Law and Civil Engineering of the Centro Universitário Assis Gurgacz-PR, contemplating the questions of Fagerström, which evaluates nicotine dependence, and they were also asked about the electronic cigarette use. In this sense, the research, which interviewed 144 students, 62 of whom were undergraduates from the Law course, 65 from Medicine and 17 from Civil Engineering, from the 1st to the 11th period, confirmed the main hypothesis of the researchers: the students, for the most part, started their smoking habit due to the practicality of the device and part of the undergraduates has already developed dependence.